2012
DOI: 10.7314/apjcp.2012.13.1.367
|View full text |Cite
|
Sign up to set email alerts
|

Increased Trend of Breast Cancer Mortality in Iran

Abstract: Background: Breast cancer is the most commonly diagnosed cancer in women worldwide In Iran, it ranks first among cancers diagnosed in women and is the fifth most common cause of death. The aim of this study was to present the mortality trends from breast cancer for Iranian women during a period of almost a decade, in order to provide update information regarding the likely future. Methods: We analyzed National death Statistic reported by the Iranian Ministry of Health and Medical Education from 1995 to 2004 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 27 publications
2
96
0
2
Order By: Relevance
“…Epidemiological studies based on age-specific incidence in Iran showed that the cancer has the highest prevalence among 45-55 years old women (Taghavi et al, 2012). As other developing countries, these studies show that breast cancer tends to accumulate among younger women in our community.…”
Section: Introductionmentioning
confidence: 70%
“…Epidemiological studies based on age-specific incidence in Iran showed that the cancer has the highest prevalence among 45-55 years old women (Taghavi et al, 2012). As other developing countries, these studies show that breast cancer tends to accumulate among younger women in our community.…”
Section: Introductionmentioning
confidence: 70%
“…Tohid Jafari-Koshki 1,2 , Marjan Mansourian 2,3 , Fariborz Mokarian 4 rank of incidence from the second to the first diagnosed cancer during these years, and it is currently the fifth most common cause of cancer death in women (Lamyian et al, 2007;Mousavi et al, 2007;Babu et al, 2011;Noroozi et al, 2011;Taghavi et al, 2012).…”
Section: Exploring Factors Related To Metastasis Free Survival In Brementioning
confidence: 99%
“…In Iran, even though the prevalence of breast cancer is lower compared to western countries, it is the most common malignancy among women (Rezaianzadeh et al, 2011). There is an increasing trend for breast cancer mortality in Iran during 1995 to 2004 from 1.40 to 3.52 per 100,000 (Taghavi et al, 2012). In the next decades, Iran will face an upsurge in the incidence of the disease (Dey and Soliman, 2010).…”
Section: Introductionmentioning
confidence: 99%